Evaluasi Program Corporate Social Responsibility: Bengkel Sampah Terhadap Masyarakat Lembah Lubuk Raya - Farhan Muhammad Irsyadi (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
Indonesia currently has a population of around 264 million people and is recorded as the country with the 4th largest population in the world. With a large population, this certainly has an impact on the amount of waste produced, which will then correlate with the amount of waste produced. Garbage workshops or Waste Banks are here to solve this problem. The focus of this research is to find out what can be improved in the waste workshop program in Lembah Lubuk Raya Village. Through research that focuses on evaluation efforts that focus on evaluation with theory that focuses on evaluating the context, input, process and results of the waste workshop program to find out what can be improved in the waste workshop program for the people of the Lubuk Raya valley. In this research, the approach used is a qualitative approach by conducting interviews, observations and documentation studies in the process. The results of the research show that the program is running well, because the program implemented has been able to change the environmental care behavior of the community in Lembah Lubuk Raya Village. However, on the other hand, there is still a need to improve the quality of program services such as discipline and the provision of facilities, namely waste chopping machines, to increase the value and benefits of the program.